Parental Responsibility for Children Placed in the Aisyiyah Orphanage Batusangkar Branch A Review of Islamic Family Law - Husna Rita; Nofialdi; Arianti, Farida; Yunarti, Sri (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
This study explores the responsibilities of parents toward children placed in the Aisyiyah Orphanage, Batusangkar Branch, through the lens of Islamic Family Law. parents are obliged to provide for and raise their children even after divorce. The 1974 Indonesian Marriage Law (Articles 45 and 41) mandates that both parents are responsible for their children’s welfare until they are self-sufficient or married. However, the reality on the ground often shows a significant gap between legal expectations and practical implementation, particularly in cases involving divorce, poverty, or remarriage. The research focuses on three issues: the reasons why parents put their children, the obstacles for parents to put their children, and the responsibility of parents for children who are put in the Aisyiyah Orphanage Batusangkar Branch. This study Used qualitative field research with a descriptive approach, data were gathered through interviews and documentation involving parents, children, and orphanage administrators. The results showed that people who put their children in orphanages had 5 reasons, namely: so that children are in a safe environment, biological fathers are reluctant to care for their children, mothers are unable to educate their children, to continue their children's education, get guidance from caregivers and administrators. There are 3 obstacles for parents to put their children in the Aisyiyah Branch Batusangkar orphanage, namely: not being fully supported by their biological father, the lack of income of parents, parents being unable to provide maintenance. For the responsibilities of parents towards children in orphanages according to the results of interviews found by researchers that there are 8 respondents who carry out their responsibilities as parents but not fully, while 2 foster children do not accept the responsibilities of parents.